CORRELATION BETWEEN OF DPT AND MEASLES IMMUNIZATION ON THE INCIDENCE OF PNEUMONIA IN CHILDREN AGED 10 MONTHS-5 YEARS IN THE CITY OF PALU SANGURARA HEALTH CENTERS IN 2015 - Vitawati, Vitawati; Sari, Puspita (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2017)
Background: Pneumonia is one of the largest contributors to health problems and causes of death of children under five years old. Pneumonia kills approximately 935,000 children under the age of five in 2013, accounting for 15% of all deaths in children under five years of age. Pneumonia in children most commonly found in children with incomplete immunization status. Immunizations are associated with the incidence of pneumonia is the pertussis immunization in DPT, measles, Haemophilus influenza, and pneumococcal.Objective: To determine the correlation of DPT and measles immunization on the incidence of pneumonia in children aged 10 months-5 years in the city of Palu Sangurara health centers in 2015.Methods: This study is a non-experimental study with cross sectional approach. The population is all pediatric patients who came to the Sangurara clinic which were as many as 1,782 children. The sample was 95 children aged 10 months-5 years, obtained by purposive sampling.Results: The results of the data analysis conducted with chi-square test to find out the correlation between DPT immunization towards pneumonia showed p value was 0,011 so that H1 is accepted. The value of phi test showed 0,260 that indicate negative correlation with the strength of the correlation is weak. Furthermore, the results of data analysis with chi square test about the correlation between measles immunization towards pneumonia found that value of p <0.05 is 0,002 so that H1 is accepted. Phi test values was 0,319 indicates that the negative correlation with the strength of the correlation was intermediate.Conclusion: There is a significant correlation between DPT and measles immunization in reducing the incidence of pneumonia in children aged 10 months-5 years in the city of Palu Sangurara health centers in 2015. Keywords: Pneumonia, DPT and measles immunizationLatar Belakang : Pneumonia membunuh kira-kira 935.000 anak di bawah usia lima tahun pada tahun 2013, terhitung untuk 15% dari seluruh kematian anak di bawah usia lima tahun. Pneumonia pada anak paling banyak ditemukan pada anak dengan status imunisasi yang belum lengkap. Imunisasi yang berhubungan dengan kejadian penyakit pneumonia adalah imunisasi pertusis dalam DPT, campak, Haemophilus influenza, dan pneumokokus.Tujuan : Untuk mengetahui hubungan pemberian imunisasi DPT dan campak terhadap kejadian pneumonia pada anak usia 10 bulan-5 tahun di puskesmas Sangurara kota Palu tahun 2015.Metode : Penelitian ini merupakan penelitian non eksperimen dengan pendekatan cross sectional. Populasi adalah semua pasien anak usia 10 bulan-5 tahun yang datang ke puskesmas Sangurara berjumlah 1.782 anak. Sampel yang digunakan berjumlah 95 anak yang berusia 10 bulan-5 tahun, diperoleh dengan cara purposive sampling.Hasil : Hasil analisa data uji chi square mengenai hubungan antara pemberian imunisasi DPT terhadap kejadian pneumonia diperoleh nilai p < 0,05 yaitu 0,011 sehingga H1 diterima. Nilai uji Phi 0,260 menunjukkan bahwa korelasi negatif dengan kekuatan korelasi lemah. Selanjutnya hasil analisis data uji chi square mengenai hubungan antara pemberian imunisasi campak terhadap kejadian pneumonia diperoleh nilai p < 0,05 yaitu 0,002 sehingga H1 diterima. Nilai uji Phi 0,319 menunjukkan bahwa korelasi negatif dengan kekuatan korelasi sedang.Kesimpulan : Terdapat hubungan yang bermakna antara pemberian imunisasi DPT dan campak dalam menurunkan kejadian pneumonia pada anak usia 10 bulan-5 tahun di puskesmas Sangurara kota Palu tahun 2015. Kata Kunci : Pneumonia, Imunisasi DPT dan campak